Study of Organizational Culture, Office Facilities, Work Motivation and Employee Performance at Class I Immigration Office TPI Malang: Literature Review - Fransisca, Herlinda; Rahadian, Candra; Arifianto, Helmi Nugroho; Rokhman, M. Taufiq Noor (PT FORMOSA CENDEKIA GLOBAL, 2024)
This literature review aims to examine organizational culture, office facilities and employee performance at the Class I TPI Malang Immigration Office. Organizational culture is defined as the values, norms, and beliefs applied in an organization, while office facilities include the physical environment and work support tools. Work motivation is identified as an internal drive that drives employees to achieve certain goals. The research method used is the Literature Review method from various sources of previous research results. From the results of the review of related research, most studies acknowledge that organizational culture, office facilities, and work motivation affect employee performance. The expected results of this study are a deeper understanding of how organizational culture, office facilities, and work motivation affect employee performance through the results of several previous studies. In addition, the study is also expected to be a consideration for organizations in making policies in terms of improving employee performance.